Introduction Surviving the Paraphrase:: Poetics and Public Culture in Canada - Brydon, Diana; Jones, Manina; Schagerl, Jessica; Warder, Kristen (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2007)
None